2006
DOI: 10.1002/nur.20137
|View full text |Cite
|
Sign up to set email alerts
|

Responding to sexual assault victims' medical and emotional needs: A national study of the services provided by SANE programs

Abstract: We measured the consistency with which a national random sample of 110 Sexual Assault Nurse Examiner (SANE) programs provided 17 services to sexual assault victims. SANE programs consistently offered forensic evidence collection, sexually transmitted infection (STI) prophylaxis, information on HIV, information on pregnancy risk, and referrals to community resources. Reasons programs did not routinely offer particular services (e.g., STI cultures, HIV testing/prophylaxis, emergency contraception (EC)) included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 29 publications
(36 reference statements)
1
66
0
Order By: Relevance
“…Survivors of SA suffer more negative psychological outcomes than other crime victims (Petrak, 2002), and might suffer from severe posttraumatic stress symptoms for years or decades following the assault (see Kiump, 2006, for review). Additional long-term outcomes associated with survivors who do not seek intervention include depression, anxiety, substance use problems, and chronic health problems (see Campbell et al, 2006;Kilpatrick & Acierno, 2003;Ullman, Filipas, Townsend, & Starzynski, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of SA suffer more negative psychological outcomes than other crime victims (Petrak, 2002), and might suffer from severe posttraumatic stress symptoms for years or decades following the assault (see Kiump, 2006, for review). Additional long-term outcomes associated with survivors who do not seek intervention include depression, anxiety, substance use problems, and chronic health problems (see Campbell et al, 2006;Kilpatrick & Acierno, 2003;Ullman, Filipas, Townsend, & Starzynski, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Health care provider surveys including frequency of offering post-sexual assault services found similar rates (38%) of reported baseline HIV testing among SANEs (Campbell et al, 2006) and EDs (Patel, Panchal, Piotrowski, & Patel, 2008), with higher rates (58-88%) for pediatric practitioners (Babl et al, 2001). In contrast, a greater proportion (41%) of a nationally representative SANE program sample (Campbell et al, 2006) reported offering nPEP than Illinois (28%; Patel et al, 2008) and Massachusetts EDs (28%; Kunches, Meehan, Boutwell, & McGuire, 2001).…”
Section: Results and Critiquementioning
confidence: 45%
“…In contrast, a greater proportion (41%) of a nationally representative SANE program sample (Campbell et al, 2006) reported offering nPEP than Illinois (28%; Patel et al, 2008) and Massachusetts EDs (28%; Kunches, Meehan, Boutwell, & McGuire, 2001). While more pediatric ED physicians and infectious disease specialists reported HIV baseline testing, a smaller proportion reported having ever offered nPEP (14-27%) (Babl et al, 2001).…”
Section: Results and Critiquementioning
confidence: 74%
See 2 more Smart Citations